SEARCH FOR AEROSOL MICROPARTICLES IN DATED LAYERS OF BOTTOM SEDIMENTS USING SYNCHROTRON RADIATION - A. V. Darin; F. A. Darin; Ya. V. Rakshun; D. S. Sorokoletov; A. A. Gogin; R. A. Senin (Геодинамика и тектонофизика, 2022)
The SR-micro-XRF method was used to search for microparticles of extraterrestrial matter in the bottom sediments of Lake Zapovednoye, located 60 km from the epicentre of the explosion of the Tunguska cosmic body (TCB) in 1908. The material of bottom sediments dating back to 1908–1910 was studied. The samples for the study were prepared in the form of a powder applied to a conductive adhesive tape, which made it possible to combine the data of optical observations, electron microscopy, and micro-XRF scanning. The experiments were carried out at the Large-Scale Research Facilities "Kurchatov Centre for Synchrotron Research" using a confocal X-ray microscope developed at the Budker Institute of Nuclear Physics SB RAS. The data obtained indicate the presence of microparticles with an increased Ni/Fe ratio, possibly of extraterrestrial origin.